New syarinid pseudoscorpions from Ecuador (Pseudoscorpiones, Syarinidae: Ideobisium and Ideoblothrus) - Amieva Mau, Sofia; Harvey, Mark S.; Harms, Danilo (European Journal of Taxonomy, 2022)
The pseudoscorpion (Arachnida: Pseudoscorpiones) fauna of mainland Ecuador, excluding the Galápagos Islands, is poorly known, with only 41 described species in 9 families. The family Syarinidae has a pantropical distribution and presently comprises ca 120 species in 17 valid genera that are found in leaf litter and subterranean habitats, mostly in tropical and subtropical climates. Four syarinid species have been recorded from Ecuador, including the Galápagos, in two widespread genera, Ideobisium and Ideoblothrus, but field collections suggest that these pseudoscorpions are common and abundant in all forest systems across the country. Here, we review field collections of syarinids from mainland Ecuador and describe five new species in these genera: Ideobisium kichwa sp. nov. (Napo Province, Colonso Chalupas Natural Reserve), I. sonqo sp. nov. (Napo Province, Colonso Chalupas Natural Reserve), I. susanae sp. nov. (Napo Province, Jatun Sacha Natural Reserve), Ideoblothrus nadineae sp. nov. (Napo Province, Colonso Chalupas Natural Reserve) and I. safinai sp. nov. (Pichincha Province, Otongachi Natural Reserve) based on morphology. These species seem to have narrow distributions and we therefore restrict the ranges of two species previously recorded from Ecuador (Ideobisium crassimanum Balzan, 1892 and Ideoblothrus costaricensis (Beier, 1931)) to their countries of origin, which is Costa Rica and Venezuela, respectively.